2020
DOI: 10.1186/s41927-020-00160-5
|View full text |Cite
|
Sign up to set email alerts
|

Web-based information on the treatment of the mouth in systemic sclerosis

Abstract: Background To categorise the content and assess the quality and readability of the web-based information regarding treatment of the mouth in systemic sclerosis. Methods An online search using three different search terms regarding the treatment of the mouth in SSc was undertaken using the Google search engine. The first 100 websites from each search were selected for analysis. Data recorded included DISCERN instrument scores along with the Journal of the American Medical Association (JAMA) benchmarks and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
5
8
1
Order By: Relevance
“…In this study, the 22 sites with online education materials related to vocal cord leukoplakia were written at readability levels above those recommended by the AMA/NIH. These results are consistent with many other readability studies that have been published within otolaryngology 7,8,20,28–33 and other specialties 34–43 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the 22 sites with online education materials related to vocal cord leukoplakia were written at readability levels above those recommended by the AMA/NIH. These results are consistent with many other readability studies that have been published within otolaryngology 7,8,20,28–33 and other specialties 34–43 …”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with many other readability studies that have been published within otolaryngology 7,8,20,[28][29][30][31][32][33] and other specialties. [34][35][36][37][38][39][40][41][42][43] Similarly, PEMAT-P understandability and actionability scores were low. The understandability score of 73.65% 6 7.05% in this study is comparable but a bit higher than that of similar studies on other topics, which reported scores ranging from 62.8% to 66.0%.…”
Section: Discussionmentioning
confidence: 99%
“…For the DISCERN categories, moderate scores were the most common, and high scores were mostly in universities or medical centers. These findings are consistent with other studies, but the percentage of high-quality websites was higher for websites in this study [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…Regarding website specialization, over 90% of the websites in this study were partly related, which is also consistent with the other studies [ 14 , 15 ]. In similar studies, the content type was mostly medical facts, and this was true even for non-implant-related topics [ 26 , 27 ]. In our studies, websites containing questions and answers were more than half of the websites compared to only 10% in the study about peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to SSc/SLE eHealth support, web-based resources are often of low quality, have inadequate readability and limited functionality. [9][10][11] Several studies demonstrate that patients with rare connective tissue diseases and their providers are interested in web-based education and support. [12][13][14] However, few online programmes focus on critical concepts of health equity, patient engagement and empowerment.…”
Section: Key Messagesmentioning
confidence: 99%